KAJIAN KAFALAH PADA KOPERASI JASA KEUANGAN SYARIAH AS–SAKINAH DI KAMAL BANGKALAN - Weni Krismawati; Robiatul Auliyah; Yuni Rimawati (Universitas Trunojoyo Madura, 2013)
The aim of this research is to explore the implementation of kafalah financing in Koperasi Jasa Keuangan Syariah (KJKS) As–Sakinah Kamal Bangkalan. This research is a descriptive qualitative research. The data was collected by unstructured interviews and documentation. It employs Miles and Huberman Model to analyzed the data which then utilizes Fatwa Sharia National Board (Dewan Syariah Nasional) No. 11/DSN–MUI/IV/2000 to investigate the implementation of kafalah financing in KJKS As–Sakinah Kamal Bangkalan. The result find that in terms of kafalah financing, KJKS AS–Sakinah Kamal has conform with the provision and control of Sharia National Board. It can be found that: (a) in kafalah financing procedure, members are charged against administration fee and supplies in an agreement with a stamp duty for legalization; (b) kafalah financing agreement is signed literally when the three parties have been agree with the statements and provision explained; (c) cooperative institution is entitled to receive fee or ujroh from members with binding and not be annulled reward.